ZWIĄZKI GENETYCZNE I NORMATYWNE PRAWA PRACY Z PRAWEM CYWILNYM - Roszewska, Katarzyna (Zeszyty Prawnicze, 2017)
The Genetic and Legal Connections between Labor and Civil Laws Summary The author analysis genetic and legal connections between the labor and civil laws. The article starts from the analysis of the contract regulated in the Roman law – locatio conductio operarum, it describes the development of industrial law from XVIII/XIX centuries, and ends with the analysis of the total separation of the labor law from the civil one. The genetic connections between these two branches of law significantly influenced the labor law, in particular they determined its obligatory character. Although the labor law constitutes a separate branch it is not entirely independent. Its development depicts a constant and strong influence of the civil law. The labor law has taken over many legal solutions of the latter one. The Labor Code expressly states that if it is not provided otherwise the Civil Code’s provisions apply accordingly, unless they are contrary to the labor law provisions (art. 300 of the Labor Law). The labor law provisions also include references to the Civil Code. Finally the author analysis the similarities between the labor law and civil law legal relationships as well as the advantages of art. 300 of the Labor Law.